Evidence-based sports sciences - Hakan Yaman (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
Evidence-based practice is a useful and necessary tool for sports science. The experience of evidence-based medical science could be useful for the implementation of this new approach. Evidence-based practices in sport sciences could also affect, in addition to the fields of training practice, such as management, legislation and education. This will allow decision making to be based on the best available scientific evidence. This review summarises approaches and models of how to apply evidence-based practice in sport science. It also shares a five-step approach with the aim of providing a practical tool. Certain conditions require starting with the practice of evidence. First, the scientific literature must answer the question. Access to scientific databases, knowing how to walk through the jungle of knowledge, mastery of English (since most papers are published in English) is mandatory. A commitment by sport science stakeholders to evidence-based practice and the removal of barriers to implementation would be a promising approach to evidence-based practice in sport science in a short period of time.